Cernere et paene tangere. Touch in Cicero's Rhetorical Writings (Altre Modernità, 2023)
After providing a brief overview of the role of touch in Latin literature and, in particular, in rhetorical texts, this paper focuses on Cicero’s works. As Cicero, like most other ancient authors, does not devote explicitly sections of his writings to this sense, the investigation is conducted on some words (verbs, adjectives and nouns) which evoke touch in his oeuvre. Special attention is paid to Cicero’s rhetorical works and what emerges is Cicero’s contribution to defining touch and its functions – the cognitive function taking pride of place – within the context of Latin abstract language and ancient philosophical thinking.
Keywords: touch; Cicero; Latin literature; rhetoric